The Harmony between Costume and Interior Design: Some Cases from Medieval to Neo-classic Era in Europe - Kavakure, Fiona (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
Costume and interior design intend to follow and have some rules in common: the accurate cutting, the precise shape and proportions, the suitable color and material, etc. In either case, the designers seek for the best way to elaborate and disguise the human body or the interior space that they get in contact with to give them a visually expressive vocabulary. The architectural body or interior only differs from the human body in terms of stability and mobility, but the two interrelate since the architectural body or interior is a design for the human body. The evolution of costume illustrates a fascinating story of human apparel. For centuries, human attire has undergone numerous changes in terms of design. This has been the same phenomenon for furniture as it plays an important role in the interior design. Besides, costume and furniture have been functional and answered to the human need of dressing, masquerading and embellishing respectively the human body and the home, especially in the Medieval and the Neo-classic era. During the Renaissance era, geometric forms and abstract ornamentation were general features in design while in Baroque style, the floral elements, dynamic forms and illusionists views were highly used. Extreme ornamentation in the Rococo interior design is also reflected in the costumes, hair designs and accessories as well as the manners of the human beings. Thus, though many are the research attempts to show the relationship between costume and interior design in various perspectives, it is still a curiosity for the researcher to search more on how the designers have achieved a harmony or interrelation between the two disciplines. Costume and interior design are two very comprehensive disciplines so the study limits itself to female costume and furniture in the courts and upper class of the Medieval to the Neo-classical period in Europe. To this end, the work uses a qualitative and correlative methodology. The theoretical and historical part regarding female costume and furniture is based on a literature review. The data collected for comparison, with a judgmental sampling method, are from readily existent visual published documentation and are analyzed with deductive approach. The outcome of this study is expected to serve as a document contribution and extension of previous works. Keywords: Costume Design, Interior Design, Furniture, Female Costume

Günlük yaşamda insanlar giysi ve iç mekan tasarımları ile iç içe temas halinde yaşar. Her birey günlük yaşamında ne giyeceği ve kendini nerede ve nasıl barındıracağı konularında sürekli bazı endişeler içinde olur. Bu arayışlar içinde de yeni tasarımlar ve keşifler yapar. Giysi ve iç tasarım insan bedeninin ve mimari yapının giydirilmesi veya donatılmasına ön ayak olan en temel ihtiyaçlarını karşılama yönünde önemli arayışlar içinde oldu. Bu araştırmanın amacı giysi tasarımı ve iç mimari tasarımının her zaman birbirlerini nasıl etkilediğini sorgulamaktır. Çalışmada, kadın giysileri tasarımının çeşitliliği ve karmaşıklığı sonucu, iç mekanlar da dönemin modasına uyarak, konfor yaratma yönünde çağlar boyu gelişmeler gösterir. Çalışma, konut iç mekanları ve kadın giysileri ile sınırlandırılmıştır. Araştırma, iç mekanlar, mobilya ve giysilerin şekil, mekan, doku ve süsleme açısında daha özenilerek, kullanıcısnda farklılık yaratma amacı ile tasarlanmaya başlandığı dönemleri kapsamaktadır. Bu çalışmanın ele aldığı tasarım alanlarının çokluğu nedeni ile niteliksel ve karşılaştırmalı bir araştırma yöntemi izlenmiştir. Bu çalışma moda tasarımında kişiye rahatlık yaratmanın ötesinde toplumda sıradışı görünme amacı ile benzer üslupta giysiler ve iç mekan tasarımlarının ortaya çıkarılması olgusunu vurgulama yönüyle önemlidir. Bu araştırmanın ayrıca profesyonel tasarımcılar için ilham kaynağı olabilmesi beklenmektedir. Anahtar Kelimeler: Giysi Tasarımı; İç Mimari Tasarımı; Mobilya; Konut İç Mekanı; Kadın Giysileri.
Master of Science in Interior Architecture. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Interior Architecture, 2015. Supervisor: Assoc. Prof. Dr. Netice Yıldız.
Keywords: Interior Architecture; Costumes and Interior Design; Costume Design - Home Design; Costume Design, Interior Design, Furniture, Female Costume